A3 Adenosine and P2X7 Purinergic Receptors as New Targets for an Innovative Pharmacological Therapy of Malignant Pleural Mesothelioma - Vincenzi, Fabrizio; Rotondo, John Charles; Pasquini, Silvia; Di Virgilio, Francesco; Varani, Katia; Tognon, Mauro (Frontiers in Oncology, 2021)
Human malignant pleural mesothelioma (MPM) is a rare, but aggressive tumor of the serosal cavities whose 5-year survival rate is 15%. At present, there are no effective therapies for MPM. Although recent findings suggest that A3 adenosine (A3AR) and P2X7 (P2X7R) receptors can be employed as antitumoral pharmacological targets in MPM, their potential role in a combined therapy is currently unknown. The A3 adenosine receptor agonist Cl-IB-MECA and the P2X7 receptor antagonist AZ10606120, as a single compound or in combination, were investigated in vitro for their anti-tumor activities. Assays were carried out in MPM cell lines IST-Mes2 and MPP89 and in primary human normal mesothelial cells (HMCs), as control. Single treatment with Cl-IB-MECA reduced cell proliferation and favored a pro-apoptotic effect in both MPP89 and IST-Mes2 cell lines, whereas AZ10606120 inhibited cell proliferation and induced apoptosis in IST-Mes2, only. The combined treatment with Cl-IB-MECA and AZ10606120 reduced cell proliferation and favoured apoptosis in MPP89 and IST-Mes2 cell lines, whereas no synergistic effect was detected. These data cumulatively suggest the absence of a synergistic effect in combined targeting of A3 adenosine and P2X7 receptors of MPM cell lines. This study may stimulate further investigations aimed at determining new combinations of antitumor compounds and more effective therapeutic strategies against MPM.